Impact of human caregiving style on the dog-human bond - Fahlgren, Anna (SLU/Dept. of Animal Environment and Health (until 231231), 2019)
Research about attachment behaviours of dogs as a response to human caregiving behaviour as well as the owner’s view of the relationship, is of relevance for the welfare of the dog and the owner. Dogs have been obser-ved showing similar attachment behaviours toward humans as seen in child-ren toward a parent. There are four different attachment styles defined wit-hin the human psychology; insecure anxious, insecure avoidant, secure and disorganised attachment. A person with one type of adult attachment style usually has a corresponding caregiving style. These caregiving styles have been applied within the anthrozoology through surveys and during studies of dog behaviour during challenging situations. The caregiving styles secure and disorganised and their impact on behaviour in Beagles in chal-lenging situations has been studied at the Swedish University of Agricultural Sciences (SLU) in 2017. In 2019, a similar study was performed with Beag-les at SLU with the two other caregiving styles, insecure avoidant and insecure anxious.